"I Mean I'm Kind of Discriminating My Own People:" A Chinese TESOL Graduate Student's Shifting Perceptions of China English. Issue 2 (15th September 2017) - Nuske, Kyle
Abstract : World Englishes has become a robust field of inquiry as scholars pursue more nuanced understandings of linguistic localization and multilinguals' negotiations of language differences. Yet research demonstrates that teachers and learners of English as a foreign language continue, albeit in a partially conflicted way, to believe that prestigious native speaker varieties are the sole acceptable targets of instruction. Thus, there is a need for further inquiries into the factors that influence individuals' attitudes toward localized Englishes and the efficacy of classroom interventions in modifying these. Utilizing a qualitative case study approach, the present study traces one Chinese TESOL graduate student's journey from harshly repudiating China English to vindicating its use. Drawing from semistructured interviews conducted over approximately 3 years, the study illustrates how the participant's language attitudes were bound up with her emotional understandings of significant life experiences. It also explicates how the complex ramifications of a blunt provocation from one of her instructors and a sense of alienation arising from studying alongside U.S. native speakers ultimately led her to defend China English outside the classroom. The article concludes with practical recommendations for TESOL programs that seek to instill more tolerant dispositions toward linguistic differences while avoiding superficial inscriptions of Western discourses.